2011
DOI: 10.5601/jelem.2011.16.3.04
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the chemical composition of the rhizosphere of tomato grown on inert substrates in a prolonged cycle

Abstract: The aim of this study, conducted in 2005-2007, was to determine changes in the chemical composition of extracts from the rhizosphere of tomatoes and of drainage water in tomato culture set up on rockwool, perlite and expanded clay and nourished with one of the two nutrient solutions containing different concentrations of macronutrients (EC I: 2.4 mS cm-1 and EC II: 3.6 mS cm-1). Perlite and extended clay were placed in foil sleeves, whose shape and volume corresponded to the weight of rockwool. The tomatoes we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Joner et al (2000) indicated that the surface area of AMF serves as adsorptive sites for heavy metal cations and this process prevents entry of toxic metals into the host plants. In hydroponic cultures, despite supplying plants with a standard nutrient solution, an increase in the concentrations of minerals in the root zone of plants has been frequently observed as an effect of accumulation (JArosz et al 2011, kleiBer 2012. It can be assumed that the limiting effect of AMF on the uptake of Zn and Cu by mycorrhized plants was the result of elevated concentrations of these components in the root zone.…”
Section: Mineral Status Of Plantsmentioning
confidence: 99%
“…Joner et al (2000) indicated that the surface area of AMF serves as adsorptive sites for heavy metal cations and this process prevents entry of toxic metals into the host plants. In hydroponic cultures, despite supplying plants with a standard nutrient solution, an increase in the concentrations of minerals in the root zone of plants has been frequently observed as an effect of accumulation (JArosz et al 2011, kleiBer 2012. It can be assumed that the limiting effect of AMF on the uptake of Zn and Cu by mycorrhized plants was the result of elevated concentrations of these components in the root zone.…”
Section: Mineral Status Of Plantsmentioning
confidence: 99%
“…While growing anthurium in expanded clay pellets, a 9.5% decrease of EC was found (KLEIBER, KOMOSA 2006). On the another hand, in an experiment with tomato grown in perlite or expanded clay pellets, the concentration of drainage waters leaking from medium was higher than in solutions applied to the plants (JAROSZ et al 2011). It seems that modifications in the composition of the rhizosphere and drainage water depend not only on the medium, but also on crop species and even on a cultivation system (DYOEKO, KOWALCZYK 2005).…”
Section: Resultsmentioning
confidence: 99%
“…It is even recommended to use chloride-free and low-sodium fertilizers in protected cultures. In this type of crop production, medium salinity is most commonly caused by excessive concentration of K + , NH 4 + , Na + , NO 3 -, SO 4 2and BO 3 3as well as Na + and Cl -, with the latter two being ballast elements in applied fertilizers (AUERSWALD et al 1999, JAROSZ et al 2011. Currently, soilless or hydroponic culture, a specific method of crop production, predominates in greenhouses and foil tunnels (GAJC-WOLSKA et al 2008).…”
Section: Introductionmentioning
confidence: 99%